The Effect of Media on the Chinese People’s Anti-Corruption Perceptions ––An Analysis Based on Propensity Score and Qualitative Interaction Tree - Zhu, Meihong; Li, Aihua (Procedia computer science, 2022)
On the basis of the survey-experiment data from 2014 to 2020, this paper investigates the effect of media coverage on the Chinese people’s anti-corruption perceptions. Propensity Score (PS) method is used for remedying covariate imbalance between trial treatment groups and control treatment group and for analyzing the main effect of media factor, and then Qualitative Interaction Tree (QUINT) method is used for estimating high-order treatment-subgroup interactions. The result shows that media coverage has a positive effect on the people’s anti-corruption perceptions, while direction and degree of media influence significantly depends on the contents of media coverage and the traits of individuals, which means there exists significant main effect and high-order treatment-subgroup interactions.